Pengaruh Program Layanan Jemput Maslahah Terhadap Intensitas Penggunaan Tabungan Mudharabah - Nisa Fajriati Nurfaridah (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
Program Layanan Jemput Maslahah is a service provided by BJB Syariah Bank to meet customer needs by visiting customers directly to accommodate customers' transaction needs quickly and easily. This research is an evaluation of a program issued by BJB Syariah Bank. This study aims to analyze the effect of the program layanan jemput maslahah, satisfaction and trust as a mediating variable on the intensity of the use of mudharabah savings. In this study the population consisted of customers in two Bank BJB Syariah Sub-Branch Offices spread across the Regency of Bandung. The samples used in this study were 125 customers of the Syariah BJB Bank in Bandung Regency. The data used is primary data in the form of a closed questionnaire. The data analysis method used is descriptive data analysis and quantitative data analysis. The tool used to analyze data in research is SmartPLS 2.0. The results of this study indicate that Layanan Jemput Maslahah has a positive influence on the Intensity of the Use of Mudharabah Savings and Satisfaction and Trust can positively mediate between Layanan Jemput Maslahah and the Intensity of the Use of Mudharabah Savings.